Intervensi Tiongkok Dalam Penegakan Hukum Illegal Fishing di Wilayah Zona Ekonomi Eksklusif Indonesia (Kasus Kapal Kway Fey 10078, Tiongkok) - Intan Kusumadewi; Anugrah Adiastuti (Faculty of Law Universitas Sebelas Maret, 2018)
This research aims to examine the law enforcement mechanisms for perpetrators of illegal fishing in the EEZ through international and national legal instruments. This research is a normative legal research that is prescriptive by using statute approach and case approach to sourch data. The results showed that the Kway Fey 10078 flagged in China captured by Kapal Pengawas Hiu 11 owned by the Indonesian government, is proven to conduct illegal fishing activities in the Indonesian EZZ. Then the actions carried out by Chinese Coast Guard ships by crashing the Kway Fey 10078 is an intervention act on the illegal fishing law enforcement process in Indonesia. The law enforcement process against the captain and crew of Kway Fey 10078 has complied with international law, which only impose penalties. Through this research, the authors will identify law enforcement against the Kway Fey 10078 Ship that violates Indonesian sovereignty.